PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI KARYAWAN DI PT BANK CENTRAL ASIA, TBK KANTOR CABANG PASAR BARU - Dini, Mutiara; Nawangsari, Lenny Christina (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
The purpose of this research is to investigate the Effect of Organizational Culture, Motivation, and Work Environment on Organizational Commitments of Employees in the Pasar Baru Bank BCA Branch, respondents who used as many as 138 employees working at PT Bank BCA Pasar Baru Branch. Data is processed using Statistical Package for Social Sciences (SPSS) Version 24. The results of this study indicate that Organizational Culture has a positive effect on Organizational Commitment, Motivation has a positive effect on Organizational Commitment and Work Environment has a positive effect on Organizational Commitment.